2020
DOI: 10.3390/healthcare8030332
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Workplace Violence and Innovative Work Behavior: The Mediating Roles of Employee Wellbeing

Abstract: It has been contended that violence is prevalent in the workplace, and there has been increasing research interest into its potential effects. Human interactions at workplaces are apparent. However, the interactions among humans may have positive or negative dimensions. Usually, the positive or negative interactions between workers lead to different outcomes. Sometimes, they lead to a productive working environment; however, in some cases, they lead to toxicity among workers. In this study, we investigate the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
56
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(62 citation statements)
references
References 79 publications
6
56
0
Order By: Relevance
“…These findings are also in line with the COR theory and RBV (resource-based-view) theory [ 6 , 67 , 73 ]. This is consistent with prior studies that have shown a negative relationship between WI and IWB [ 7 , 77 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These findings are also in line with the COR theory and RBV (resource-based-view) theory [ 6 , 67 , 73 ]. This is consistent with prior studies that have shown a negative relationship between WI and IWB [ 7 , 77 ].…”
Section: Discussionsupporting
confidence: 93%
“…According to previous studies, workplace ostracism and workplace incivility decrease organizational performance and innovative work behavior [ 3 , 6 , 7 ]. This problem of performance affected by WO and WI got the attention of researchers to investigate and address this issue with higher consideration to identify the roots and causes of WO and WI for the organization, as well as for other stakeholders [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…The results of their study confirmed that a toxic workplace environment has a negative connection with employee engagement, which reduces the individual worker’s productivity. The findings of this research are also supported by COR theory [ 55 ]. Furthermore, it is also noted that the workers’ health is affected by high job demands and work pressures; as a result, effects such as headaches, personality disorders, anxiety disorders, insomnia, burnout, and depression occur.…”
Section: Discussionsupporting
confidence: 85%
“…Samma, Zhao [ 2 ] examined 254 workers employed at small and medium-size enterprise (SMEs) located in Pakistan, and the outcomes of their study indicated that a toxic workplace environment negatively influences employee well-being. Specifically, in this relationship, COR theory confirms that most of SMEs are facing workplace violence, which brings about a negative attitude among the workers, which negatively affects the balanced and emotional well-being connection with the vision and mission of the organization [ 55 ]. Moreover, in this study, we tested the positive relationship between employee well-being and employee engagement.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation